High-precision, real-world modeling of a semi-automatic powertrain. (September 2014) - Pasdar, Amir Hossein; Azadi, Shahram; Kazemi, Reza
In a mechatronical approach, the design of a highly detailed, physically based model of a semi-automatic powertrain suitable for supervision has been explicated. In each part of the powertrain system, ultimately developed dynamical models have been exploited to make sure the whole model is up-to-date and is close to a real system. Advanced dynamical equations of an engine, a clutch, a gearbox and a driveline as well as a tire and a vehicle dynamic model for analyzing longitudinal performance have been considered. A well-suited automated manual transmission (AMT) along with a mean value transient spark-ignition (SI) engine model has been inserted to complete the solution. In order to simulate a real vehicle, the nonlinearities of the powertrain system mainly generated in the engine and clutch have drawn attention. Transient behavior of the system is a key parameter for design; hence, both steady-state and transient modeling such as of the gear shift procedure were considered. All parts of the model have been verified against experimental data. Finally, an overall simulation of the powertrain and vehicle in an in-city Economic Commission for Europe (ECE) cycle and a complete involved simulation of a gear shift process using Simulink have been performed to examine the level of the modeled dynamics. Lastly, it will be clear that use of nonlinear and real-world models can enhance the modeling and make it comparable to a real system.